Perbandingan Sistem Hidrotermal Air Panas Ciater dan Palimanan: Analisis berdasarkan Komposisi Hidrogeokimia - Zulis Septian; Wirandika Mayzzani Hadiana; Fildzah Ayunda; Mary Agustina Putri; Irwan Iskandar (OPHIOLITE: Jurnal Geologi Terapan, 2025)
This study compares hot water hydrothermal systems in two locations in West Java, namely Ciater (Subang) and Palimanan (Cirebon), based on hydrogeochemical composition. Ciater, located at the foot of Mount Tangkuban Parahu, is affected by active volcanic activity, while Palimanan is in a carbonate-rich sedimentary basin area. The results of the in-situ measurements showed significant differences in pH, temperature, TDS, salinity, and DO between the two sites. Ciater has an acidic pH, stable temperature, as well as high TDS and salinity, reflecting volcanic influences, while Palimanan has a neutral pH, higher temperatures, and fluctuations in TDS and salinity, which are affected by carbonate rocks. Ion analysis showed that Palimanan hot water is dominated by chloride anion (Na-Cl), while Ciater by sulfate anion (Ca-SO₄). Heavy metals testing revealed higher concentrations of metals in Ciater, reflecting interactions with volcanic rocks, whereas Palimanan has a low metal content. The results of isotope analysis showed that the hot water in Ciater tended to mix with rainwater, while Palimanan showed significant interactions with minerals, especially carbonates. This study provides important insights into the differences in hydrothermal systems at the two sites and their implications for the utilization of geothermal resources.